Cost of illness of spinal muscular atrophy (SMA) in Italy. (August 2019) - Marcellusi, Andrea; Bini, Chiara; Casiraghi, Jacopo; D'Ambrosio, Francesco; Rotundo, Maria A.; Pallara, Anita; Mennini, Francesco S.
The objective of this study was to estimate the indirect and direct non-health costs associated with spinal muscular atrophy (SMA), a disease that burdens the daily life of adults, children and their families in Italy. In order to develop the economic model, a multidisciplinary group of researchers was created to prepare and computerize a questionnaire, which was promoted by SMA families in collaboration with the Economic Evaluation and Heath Technology Assessment center at the University of Rome Tor Vergata. The analysis envisaged a first phase for implementing and validating the questionnaire by the multidisciplinary group. Subsequently, the questionnaire was computerized and sent out to be completed through all the association's distribution channels. The social channels and specific mailing lists were limited exclusively to SMA families. To achieve the sample number required by the research protocol, data collection began on January 8, 2018, and closed on April 15, 2018. Finally, all the data were analyzed using the economic model in order to estimate the average costs per patient.The questionnaire was able to identify a sample of 118 families (22.88% SMA I, 48.31% SMA II, 28.81% SMA III). The average age of the patients was 18.49 years (average age at diagnosis 2.88 years) with more females (55, 08%) in the total respondents, taking into account a 4.24% rate of non-respondents. The economic model estimated an average annual cost per patient with SMA of €15.371, 41 (€17.683, 85 for SMA I, €15.974, 78 for SMA II and €12.523, 52 for SMA III). Of these costs, about 52% were attributable to indirect costs associated with caregivers, 15% for indirect costs associated with the patient and 4% for social security costs. A total of 17% was attributable to the direct costs incurred by the patient and 12% was attributable to the direct costs incurred by the Italian National Health Service (SSN).To our knowledge, this survey represents the first nationwide analysis estimating the costs incurred by families for the management of SMA. This study highlights the need for specific policies to support families who must live with the disease, not only from the standpoint of their compromised quality of life but also due to the significant economic burden imposed by the disease.